Analisis Faktor Yang Berhubungan Dengan Waktu Tanggap Pada Pasien Gawat Darurat Di Instalasi Gawat Darurat (IGD) RSUD A.Wahab Sjahranie Samarinda - Wiyadi Wiyadi; Gajali Rahman (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2020)
Emergency Department (ED) is the gateway for entry of patients experiencing emergency department. The services provided by the emergency room are services that require fast, precise and careful handling in determining the emergency priorities of patients to prevent disability and death. The purpose of this research is to analyze the factors related to the response time of emergency patients in ED Hospital A.W Syahranie by using observational or descriptive designs. The design of this study was cross-sectional with accidental sampling method with a sample size of 323 respondents. The results of the study were analyzed univariate, bivariate and multivariate to look for the dominant factor in emergency response time in the emergency room at A.W Syahranie Hospital Samarinda. Univariate analysis looking for percentage and bivariate analyzed with Chi Square test while multivariate with logistic regression. The results obtained P value> 0.05 for factors of payment methods, attendance of staff, staff placement patterns, availability of brankers, and shifts and the value of P <0.05 for factors of patient arrival time, patient priorities, nurse tenure and nurse education level. The conclusion from the multivariate test found that the most dominant factor related to response time was the length of service of the nurse. Keywords: factors, response time